DEVELOPMENT AND FUNCTIONING OF CHILDREN-SPECIALIZED MASS MEDIA IN UZBEKISTAN - Raximova G. Z. (TARIXIY TADQIQOTLAR, 2026)
This article examines the stages of formation and development of children’s press in Uzbekistan. It provides a detailed analysis of children’s newspapers and magazines that have operated during the post-independence period, particularly the publications “G‘uncha,” “Gulxan,” “Tong yulduzi,” and “Klass!”, focusing on their history, objectives, thematic directions, and educational significance. The article also presents information on private children’s publications and television channels for children that emerged during the years of independence. Special emphasis is placed on the role of children’s media in fostering patriotism, spirituality, and humanistic values among the younger generation.